2015
DOI: 10.5606/archrheumatol.2015.5639
|View full text |Cite
|
Sign up to set email alerts
|

Increased Carotid Intima-Media Thickness in Female Patients With Fibromyalgia: A Preliminary Study

Abstract: Objectives: This study aims to measure the carotid artery intima-media thickness (IMT) of patients with fibromyalgia (FM) by using ultrasound imaging and to investigate whether carotid IMT measurements were associated with the severity of FM. Patients and methods: Nineteen female patients (mean age 42.9±8.1 years; range 24 to 57 years) and 17 healthy female subjects (mean age 41.5±6.3 years; range 33 to 57 years) were included in this study. The Fibromyalgia Impact Questionnaire was used to determine the sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In the literature, studies have shown the presence of early atherosclerosis with increased CIMT values in ankylosing spondylitis, rheumatoid arthritis and Behçet's disease compared to a healthy population (26,27). In addition, high serum endocan levels and increased CIMT in patients with FMS have been shown in different studies (28,29) . Previous studies have reported that endocan levels and CIMT are correlated in inflammatory diseases (7,8).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the literature, studies have shown the presence of early atherosclerosis with increased CIMT values in ankylosing spondylitis, rheumatoid arthritis and Behçet's disease compared to a healthy population (26,27). In addition, high serum endocan levels and increased CIMT in patients with FMS have been shown in different studies (28,29) . Previous studies have reported that endocan levels and CIMT are correlated in inflammatory diseases (7,8).…”
Section: Discussionmentioning
confidence: 92%
“…Fibromyalgia syndrome (FMS) is a chronic Pain syndrome characterized by widespread pain, sensitivity, sleep disturbance, fatigue, cognitive dysfunction, and emotional stress (1). Although the pathophysiology of FMS has not yet been completely elucidated, it has been suggested that inflammation and endothelial dysfunction occur in patients with FMS (2,3). Studies have shown that serum levels of proinflammatory cytokines (TNF-a, IL-6) and chemokines (Tarc, MIG) are higher in patients with FMS than in the healthy population (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroendocrine abnormalities including autonomic dysfunction were thought to play an important role in the pathogenesis of the disease [3,4]. Autonomic dysfunction characterized by sympathetic hyperactivation and/or parasympathetic dysfunction in FMS patients has been shown to be related to many cardiovascular diseases including arrhythmias, and suggested to be the cause of increased cardiovascular mortality and morbidity [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Previous studies have established that FM is associated with cardiovascular diseases such as nondipper circadian blood pressure variability, increased carotid intima media thickness, and coronary heart disease. [3][4][5] Although the exact physiopathology is not known, the aforementioned studies mainly focused on inappropriate sympathetic discharges due to the autonomic nervous system changes and their impacts on blood pressure and cardiac functions. On the other hand, diastolic dysfunction (DD) refers to a collection of mechanical problems in the contraction and relaxation of the heart.…”
mentioning
confidence: 99%